Selective in vitro cytotoxic effects of piroxicam and mefenamic acid on several cancer cells lines. - Somchit, M.N; Ahmad, Zuraini; Hussain, Mohd Khairi; Ab. Hamid, Hasiah; Zakaria, Zainul Amiruddin; S, Faizah (Medwell Publishing, 2009)
Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) are heterogenous group of compounds used to cure and prevent inflammation. It was demonstrated that NSAIDs has the ability to inhibit the viability of colon cancer cells in vitro. We investigated the effects of Piroxicam and mefenamic acid on the viability of 4 cancer cell lines in which 2 of them are colon cancer cell lines (HCT 116 and CaCo-2). Cell viability was determined using MTT assay. Both NSAIDs was observed to markedly decrease the cell viability of both cell lines (HCT 116 and CaCo-2). Piroxicam was statistically more cytotoxic towards the cancer cell lines when compared to mefenamic acid. However, the cytotoxic effect of NSAIDs was less potent on breast cancer cells (MCF-7) and liver cancer cells (Hep G2). In conclusion, piroxicam and mefenamic acid showed selective cytotoxic effects against colon cancer cells but not against liver or breast cancer cells.